Coexistencia normativa en el CERESO General Francisco J. Mújica de Morelia, Michoacán - Martínez Reyes, Julio (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
This research is an interdisciplinary study, same makes consist of the study with respect to if the right to reproduce the prisoners within the municipal cereso of Morelia, Michoacán, known as "General Francisco J. Mujica". It can be considered as such, i.e. If the form in that the prisoners are governed and legally established by the State and municipal government staff should be considered as a right; This theory, must necessarily be analyzed and developed from an anthropological, sociological and historical study. In this context of ideas, this research, is rich in the theme of interdisciplinarity in the study of law, as he discusses the co-existence of systems of living contrary to those established by State legislation, same that in the foreground are contradictory, as from the legaloide point of view, they cannot, nor should there be extra-legal norms, as these latest threaten the monopoly that has the State, regarding the creation and application of laws, therefore, examines this case from a sociological, anthropological and historical perspective the above, for purposes of determining if the right that reproduces and generated internally from the cereso General Francisco J. Mujica, from the municipality of Morelia Michoacán, should be considered as such. This phenomenon is deeply analyzed from the inside of the detention centre, in order to know, understand, and understand the interaction between social actors that make up this all society, and which give rise to different normative systems extra-legal. We know that in the city of Morelia, Michoacán, cereso called General Francisco J. Mujica, as in the majority of the cherry trees that are established in the Mexican Republic, reproduces practices policy inside of these institutions, prison that make up and regulate all life and which are non-legally established prison regulations.

La presente investigación es un estudio interdisciplinario, misma que se hace consistir en el estudio respecto de si el Derecho que reproducen los presos dentro del cerezo municipal de Morelia, Michoacán, denominado “General Francisco J. Mujica”. puede ser considerado como tal, es decir, si la forma en que se rigen los presos y el personal legalmente establecido por el gobierno estatal y municipal debe ser considerado como Derecho; esta teoría, necesariamente debe ser analizada y desarrollada a partir de una estudio antropológico, sociológico e histórico. En este contexto de ideas, la presente investigación, es rica en el tema de la interdisciplinariedad en el estudio del Derecho, pues en él se analiza la coexistencia de sistemas de convivencia contrarios a los establecidos por la legislación estatal, mismos que en un primer plano son contradictorios, pues desde el punto de vista legaloide, no pueden, ni deben existir normas extralegales, pues estas últimas atentan contra el monopolio que tiene el estado, respecto de la creación y aplicaciones de las leyes, por ello, se examina este caso desde una perspectiva sociológica, antropológica e histórica, lo anterior, para efectos de determinar si el Derecho que se reproduce y que generan los internos del cereso General Francisco J. Mujica, de la municipalidad de Morelia, Michoacán, debe ser considerado como tal. Este fenómeno, es analizado profundamente desde el interior de dicho centro de reclusión, con la finalidad de saber, entender y comprender la interacción entre los actores sociales que conforman esta sociedad intra carcelaria, y que dan origen a diversos sistemas normativos extralegales.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2014-1400; Coexistencia; Normativa; CERESO; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/587